Development of young mixed Norway spruce and Scots pine stands with juvenile stand management in Finland. Issue 5 (4th July 2021) - Bianchi, Simone; Huuskonen, Saija; Hynynen, Jari; Oijala, Teppo; Siipilehto, Jouni; Saksa, Timo
ABSTRACT: In Fennoscandia, mixtures of Norway spruce ( Picea abies Karst.) and Scots pine ( Pinus sylvestris L.) are of increasing interest, since they may deliver simultaneously a wide variety of benefits. However, there is still lack of information on how young mixed stands in managed production forests would develop under even-aged management with artificial regeneration of spruce. We inventoried ten such stands (age range: 8–26), with soil properties, tree characteristics, and locations recorded in three plots. In each plot, five sample trees of both species were selected, and their past diameter and height growth were reconstructed through stem analysis. We compared species-specific mean stand parameters, and we modeled the individual tree growth. Spruce and pine had reached similar mean size, with only slight differences. The spatial distribution of the two species was even across the plots. Only 8% and 1%, respectively, of the total pine and spruce trees were damaged, with browsing the most common damage cause (62% for pine). The modeling results suggest that pine had only a small competitive advantage on spruce, and less so in higher fertility sites. Our observations showed that it is possible to develop single-storied pine–spruce mixture with the help of careful management.